The experience of open access youth work: the voice of young people. (16th March 2017) - Ritchie, Daisy; Ord, Jon
ABSTRACT: This research explores young people's experiences of open access youth work and identifies what they consider to be its value. The detailed analysis of the data, achieved through focus groups, revealed that 'association' was a key driver of engagement. It also highlighted the support system the youth club creates amongst the peers. The young people also valued the relationships they form with youth workers and acknowledge the support and guidance offered to them which better enables them to reflect on and navigate their complex lives. Young people also valued the acceptance they feel from the community developed in the youth space. It provided comfort and reassurance when at times they do not feel like they fit in anywhere else. This research offers a significant counter to the tide of current targeted youth work policy which is resulting in the demise of a provision which, judged by the findings from this research, appears to be highly valued by, and beneficial to, young people.